SYNTHESIS AND CHARACTERIZATION OF CRAB SHELL CHITOSAN SOLID ELECTROLYTE POLYMER (SPE) MEMBRANE - Mu'ayanah; Multazam; Ndruru, Sun Theo C.L. (UIN Mataram, 2024)
Efforts to prevent a global energy crisis by using renewable and environmentally friendly energy. Batteries are an alternative to replace non-renewable energy. However, in the battery, there is an electrolyte component which when finished using the battery will cause waste that causes the soil to become toxic. This study aims to determine the characterization of chitosan solid electrolyte membranes, in crab shells. The characterization carried out is the characterization of crab shell chitosan using an FTIR spectrophotometer, ion conductivity analysis of solid electrolyte membranes using an LCR Meter, and tensile tests using Tensilon. The method used in this research is experimental. Isolation of chitin and chitosan from crab shells was carried out in several stages, namely deproteination, demineralization, and deacetylation. The chitosan-lithium membrane was prepared by casting method with the addition of 15% lithium salt. The value of the degree of deacetylation in crab shell chitosan is around 39.39%. Based on the characterization, the chitosan-lithium SPE membrane conductivity value is 1.11 x 10-7 S.cm-1 with a tensile strength value of 27.07 MPa.